WORK-FAMILY BALANCE AS THE MAIN PILLAR OF FAMILY POLITICS (Annual of the Faculty of Philosophy in Skopje, 2020)
In the article, we provide an overview of the literature on work-family balance,including a discussion of the major causes and outcomes or work-family balance. Thisarticle introduces work-family border theory - a new theory about work-family balance.This article formulates a conceptual model that links work, family, and boundary-spanning demands and resources to work and family role performance and quality.To address the challenges that working parents carers face in reconciling work andfamily responsibilities, the European Commission proposed the „Work-life balance“Initiative in April 2017. This initiative is a key deliverable of the European Pillar ofSocial Rights. The Directive on work-life balance sets some new or higher standards forparental, paternity and carers leave, and the right to request flexible working arrangements.In this study, we clarify what politics are known in European Union memberstates. Here, we analyse the importance of introducing family-friendly policies, for thework-family balance and what the best policy recommendation to our country are. Thearticle closes with suggestions for further work for Macedonian family-friendly policies.
Keywords: LABOR MARKET; WORK; BALANCE; PARENTS; FAMILY